Motivasi Belajar IPA Siswa Melalui Penerapan Model Pendekatan Konflik Kognitif di Kelas VIIIB SMP Negeri 8 Kunto Darussalam - Yustini Yustini (Journal of Pedagogy and Online Learning, 2022)
This study aims to determine the increase in learning motivation of class VIIIB students of SMP N 8 Kunto Darussalam on the subject matter of pressure by using a cognitive conflict approach model. The subjects studied were students of class VIIIB, totaling 20 people. The research instrument is a learning device and a data collection instrument in the form of motivational questionnaires before and after learning. In analyzing the data, descriptive analysis techniques and inferential analysis were used. From the results of the descriptive analysis, it was found that students' learning motivation for the interest category increased by 13.2%, the relevance category increased by 6.5%, the expectation category increased by 4.2%, and for the outcome category it increased by 3.8%. From the results of inferential analysis using the sigt test, the P value <0.05, i.e. 0.000114 <0.05, which means the research hypothesis is accepted, namely there is a significant difference in science learning motivation in class VIIIB SMP Negeri 8 Kunto Darussalam on the subject of pressure through the application of the cognitive conflict approach model at the level of confidence 95%.